1999
DOI: 10.1590/s0004-282x1999000500006
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic lateral sclerosis: clinical analysis of 78 cases from Fortaleza (Northeastern Brazil)

Abstract: -We report on the clinical characteristics of amyotrophic lateral sclerosis (ALS) in Fortaleza (Northeastern Brazil). For this, we analyzed retrospectively (from 1980 to 1999) 78 cases of ALS from the Service of Neurology of the University Hospital of Fortaleza diagnosed clinically and laboratorially (EMG, muscle biopsy, myelography, blood biochemistry, muscle enzymes and cranio-cervical X-ray). The results showed that they were mostly sporadic ALS (76/78), and they were divided into definite (n= 36), probable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0
6

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 20 publications
(24 reference statements)
0
22
0
6
Order By: Relevance
“…Although FVC has been considered the most reliable tool to monitor respiratory function in patients with ALS, it is not as useful to estimate strength of respiratory muscles 20,21 . FVC is not a sufficiently sensitive test to detect early respiratory involvement in ALS, and there is only a weak correlation between FVC and parameters such as MIP and MEP 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Although FVC has been considered the most reliable tool to monitor respiratory function in patients with ALS, it is not as useful to estimate strength of respiratory muscles 20,21 . FVC is not a sufficiently sensitive test to detect early respiratory involvement in ALS, and there is only a weak correlation between FVC and parameters such as MIP and MEP 22 .…”
Section: Discussionmentioning
confidence: 99%
“…10 In 1999, a retrospective study performed on 78 patients from Ceará (a northeastern state) found 21% of them to be of juvenile (15-29 years old) sporadic form. Ninety-one percent had spinal onset, and malefemale ratio was 1.8/1 11 …”
mentioning
confidence: 99%
“…Brazilian's series of ALS shows a higher prevalence of ALS in males and the age of disease onset age around the fourth decade, except in the series of Castro-Costa and coworkers that showed a high percentage of young cases, sporadic juvenile and early-onset adults with ALS 9 . In Brazil, limb onset is more frequent and survival after diagnoses lasts around 48 months 3,[9][10][11] .…”
mentioning
confidence: 95%
“…In Brazil, limb onset is more frequent and survival after diagnoses lasts around 48 months 3,[9][10][11] . Our patient presents particular characteristics: a female native manifesting a disease occuring in earlier age.…”
mentioning
confidence: 99%